How users responded to a responsive dictionary : the case of the thesaurus of modern Slovene - Arhar Holdt, Špela (Array, 2020)
The Thesaurus of Modern Slovene is a responsive dictionary: it is compiled automatically from existing language resources while further developments of the dictionary include user participation. Many of the features introduced by the responsive model are new to the Slovene language community (e.g. data is extracted automatically and includes some errors; nonexperts are involved in dictionary compilation; the resource is never truly finished). With financial support from the Slovene Ministry of culture, a survey was conducted to gauge (potential) user opinions on the new features. The paper presents the results of the survey (n = 671) including statistical analyses of dependencies between the respondents’ opinions and their reported familiarity with the new dictionary, their age, and their professional occupation.